Effect of the nozzle tip's geometrical shape on electrospray deposition of organic thin films. (1st March 2017) - Ueda, Hiroyuki; Takeuchi, Keita; Kikuchi, Akihiko
Abstract: Electrospray deposition (ESD) is a favorable wet fabrication technique for organic thin films. We investigated the effects of the nozzle tip's geometrical shape on the spraying properties of an organic solution used for ESD. Five types of cylindrical metal nozzles with zero (flat end) to four protrusions at the tips were prepared for depositing a solution of a small-molecule compound, tris(8-hydroxyquinolinato)aluminum (Alq3 ) solution. We confirmed that the diameter of the deposited droplets and their size dispersion decreased with an increase in the number of protrusions. The area occupation ratio of small droplets with a diameter smaller than 2 µm increased from 21 to 83% as the number of protrusions was increased from zero to four. The surface roughness root mean square of 60-nm-thick Alq3 films substantially improved from 32.5 to 6.8 nm with increasing number of protrusions.